The challenges faced by small & medium sized enterprises (SMEs) in accessing credit in Tanzania: perspectives in the time of Covid-19 - Tarimo, Asha (Graduate School of Business (GSB), 2026)
This dissertation explores the financing challenges faced by small and medium-sized enterprises (SMEs) in Tanzania during the Covid-19 pandemic. Employing a qualitative research design with interviews with representatives from SMEs and financial institutions, the study explored the perspectives of SMEs seeking financing (demand side) and financial institutions offering it (supply side). The thematic findings reveal that SMEs, especially those in sectors such as hospitality, tourism and trade, encountered intense challenges due to revenue declines, asset depreciations and increased risk perceptions among lenders. SMEs reported experiencing onerous information requirements, stringent terms, increased collateral requirements, and reduced access to financing during the pandemic, these insights were however not the same for the health sector as some SMEs indicated favourable experiences in accessing financing during the pandemic period. The study also found a gap in SME awareness of government support programs with most participants unaware of initiatives like the Bank of Tanzania's Covid-19 liquidity facility, suggesting a need for improved outreach and communication in future crisis events. On the financing side, financial institutions demonstrated a cautious financing approach due to economic uncertainty and falling business activity with priority being on risk reduction through prioritizing low-risk clients and protecting financial institutions through enhanced financing conditions and collateral. The research concludes that Tanzanian SMEs faced increased challenges in accessing financing during the pandemic due to economic uncertainty, reduced revenues, increased risk perception of SMEs by financial partners, inadequate and ineligible collateral and the lack of comprehensive support programmes to uniquely support SMEs over the course of the pandemic. Recommendations emphasize improved support from development partners and the government for SMEs and the financial institutions that support SMEs during crisis events to ensure a resilient SME sector. Future studies could expand by investigating sector-specific impacts and exploring quantitative approaches to measure the financing challenges of SMEs more broadly during crisis periods.